Sinomenine Inhibits the Progression of Rheumatoid Arthritis by Regulating the Secretion of Inflammatory Cytokines and Monocyte/Macrophage Subsets - Liu, Weiwei; Zhang, Yajie; Zhu, Weina; Ma, Chunhua; Ruan, Jie; Long, Hongyan; Wang, Yue (Frontiers in Immunology, 2018)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory arthropathy associated with articular damage and attendant comorbidities. Even although RA treatment has advanced remarkably over the last decade, a significant proportion of patients still do not achieve sustained remission. The cause of RA is not yet known despite the many potential mechanisms proposed. It has been confirmed that RA is associated with dysregulated immune system and persistent inflammation. Therefore, management of inflammation is always the target of therapy. Sinomenine (SIN) is the prescription drug approved by the Chinese government for RA treatment. A previous study found that SIN was a robust anti-inflammation drug. In this study, we screened the different secretory cytokines using inflammation antibody arrays and qRT-PCR in both LPS-induced and SIN-treated RAW264.7 cells followed by evaluation of the ability of SIN to modulate cytokine secretion in a cell model, collagen-induced arthritis (CIA) mouse model, and RA patients. Several clinical indexes affecting the 28-joint disease activity score (DAS28) were determined before and after SIN treatment. Clinical indexes, inflammatory cytokine secretion, and DAS28 were compared among RA patients treated with either SIN or methotrexate (MTX). To explore the mechanism of SIN anti-inflammatory function, RA-associated monocyte/macrophage subsets were determined using flow cytometry in CIA mouse model and RA patients, both treated with SIN. The results demonstrated that SIN regulated IL-6, GM-CSF, IL-12 p40, IL-1α, TNF-α, IL-1β, KC (CXCL1), Eotaxin-2, IL-10, M-CSF, RANTES, and MCP-1 secretion in vivo and in vitro and reduced RA activity and DAS28 in a clinical setting. Furthermore, SIN attenuated CD11b+F4/80+CD64+ resident macrophages in the synovial tissue, CD11b+Ly6C+CD43+ macrophages in the spleen and draining lymph nodes of CIA mice. The percentage of CD14+CD16+ peripheral blood mononuclear cells was reduced by SIN in RA patients. These data indicated that SIN regulates the secretion of multiple inflammatory cytokines and monocyte/macrophage subsets, thereby suppressing RA progression. Therefore, along with MTX, SIN could be an alternative cost-effective anti-inflammatory agent for treating RA.